1901 Kan. Gen. Stat. 1003, 1141 - (:unkn) unknown (My University, 1901)
Ch. 19, Art. 3, §§ 748: The council may prohibit and punish the carrying of fire arms or other deadly weapons, concealed or otherwise, and may arrest and imprison, fine or set at work all vagrants and persons found in said city without visible means of support, or some legitimate business
Keywords: CARRY